Financial control between Rashidun Caliphs and the late 11th century - Mohammad Ismail, Bassem; ., Hamidah (Khatulistiwa, 2019)
Many modern concepts of financial control and its types that are now adopted have already existed in the Islamic state from Prophet Muhammad message through the Rashidun Caliphs and then the Umayyad and Abbasid through establishing Baitul Mal. This article try to investigate the concept of financial control and types in Islam and the historical development of financial control in Islam. Also clarify the principles of financial control in Islam. The research based on the descriptive approach through the use of scientific studies which dealt with the subject of research, in addition to the historical approach through the use of historical evidence in the way enhancing the opinions presented by the research in the rooting of its themes from the Islamic point of view. This paper give an attention to the behavioral principle and self-control of individuals when working in different areas of life in general and financial in particular, as they have direct causes of increased efficiency and effectiveness financial control system.